Optimization of off-centered lens parameters in high-power stimulated Brillouin-scattering phase-conjugation mirror - Wang, Hongli; Liu, Chaoshuai; Jiang, Tianrun; Li, Kaiyang (Frontiers in Physics, 2025)
The rotating off-centered lens method serves as a crucial role for improving the performance of high-power stimulated Brillouin-scattering phase-conjugation mirrors (SBS-PCMs). A practical method based on optimization parameters of off-centered focusing lenses was proposed to mitigate laser spot distortion due to thermal effects. The influence of off-centered lens parameters on the beam intensity pattern at the focal point is simulated and analyzed using the ray tracing method. Experimental results demonstrate that implementing a rotating off-centered lens configuration with optimized parameters (150 mm focal length and 6 mm decentration) achieves significant reduction in coma aberration. This study can provide valuable experimental references for the application of SBS-PCMs in high power and high-repetition rate laser systems.